VERSIONS OF THE EPIC "GOROGLY" BASED ON THE RESEARCH OF KARL REICHL (Scientific journal of the Fergana State University, 2023)
The article discusses the scientific research of the famous German scientist Karl Reichl on the versions of the epic "Gorogly", which is popular among Turkic and non-Turkic peoples.